2021
DOI: 10.1021/acsami.1c05614
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional (3D) Laser-Induced Graphene: Structure, Properties, and Application to Chemical Sensing

Abstract: Notwithstanding its relatively recent discovery, graphene has gone through many evolution steps and inspired a multitude of applications in many fields, from electronics to life science. The recent advancements in graphene production and patterning, and the inclusion of two-dimensional (2D) graphenic materials in three-dimensional (3D) superstructures, further extended the number of potential applications. In this Review, we focus on laser-induced graphene (LIG), an intriguing 3D porous graphenic material prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
136
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(139 citation statements)
references
References 102 publications
3
136
0
Order By: Relevance
“…It can also be easily stretched and coated on the surface of various materials and in different forms, and recent studies have also confirmed its bactericidal and bacteriostatic properties [ 6 , 24 , 25 ]. These unique properties mean that graphene has great potential and it has already been successfully applied in many fields, such as the automotive industry, aerospace, electrical engineering, robotics, solar cells, energy storage, telecommunications, biochemistry and medicine [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. These advantages make it possible to use graphene for stabilization and structure reinforcement of polymers that have certain limitations; i.e., natural polymers such as starch, chitosan, cellulose, alginates, hyaluronic acid, which, despite their many advantages, show weak barrier properties or poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be easily stretched and coated on the surface of various materials and in different forms, and recent studies have also confirmed its bactericidal and bacteriostatic properties [ 6 , 24 , 25 ]. These unique properties mean that graphene has great potential and it has already been successfully applied in many fields, such as the automotive industry, aerospace, electrical engineering, robotics, solar cells, energy storage, telecommunications, biochemistry and medicine [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. These advantages make it possible to use graphene for stabilization and structure reinforcement of polymers that have certain limitations; i.e., natural polymers such as starch, chitosan, cellulose, alginates, hyaluronic acid, which, despite their many advantages, show weak barrier properties or poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, more than a hundred research publications and several review papers have been devoted to the electroanalytical application of LIG electrodes [14][15][16][17]. The current review is also devoted to analyzing works on the role of LIG electrodes in electroanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, scientists are more concerned about the miniaturization of supercapacitors and have been working to create micro supercapacitors (MSCs) with the same high power density, fast charging and discharging speed, and long cycle life as conventional supercapacitors. [41][42][43][44][45] Notably, one of the difficulties encountered in the development of MSCs is that for macroscopic supercapacitors, negligible physical effects suddenly become apparent at the microscopic size, which is the law of scale. Likewise, Ppy, a common polymer electrode material, is no exception.…”
Section: Introductionmentioning
confidence: 99%